Optimal Taxation and Debt with Uninsurable Risks to Human Capital Accumulation - GOTTARDI, Piero (Institutional Knowledge at Singapore Management University, 2015)
We consider an economy where individuals face uninsurable risks to their human capital accumulation and analyze the optimal level of linear taxes on capital and labor income together with the optimal path of government debt. We show that in the presence of such risks, it is beneficial to tax both labor and capital and to issue public debt. We also assess the quantitative importance of these findings, and show that the benefits of government debt and capital taxes both increase with the magnitude of idiosyncratic risks and the degree of relative risk aversion.